Smart Magnetic Drug Delivery System for Targeted, Intracellular Delivery of Irinotecan and Platinum-Based Antitumoral Drugs - Motelica, Ludmila; Vasile, Bogdan Stefan; Ficai, Denisa; Oprea, Ovidiu-Cristian; Surdu, Vasile Adrian; Trusca, Roxana Doina; Spoiala, Angela; Voicu, Geanina; Anghelache, Maria; Marta, Daciana Silvia; Peteu, Victor-Eduard; Ficai, Anton; et al. (MDPI, 2026)
Coated magnetic nanoparticles (MNPs) comprising Fe3O4 are a powerful drug delivery system for cancer treatment. They can be preferentially internalized into the tumour cells and release the antitumoral agents on-site. In the present work, we have functionalized the MNPs with glutamic acid which, even if non-essential, is strongly involved in the protein synthesis as a nitrogen donor, being used as a conjugate for specific antitumoral drugs due to its capability to internalize into tumour versus healthy cells faster. The functionalized MNPs were stabilized by polyethylene glycol (PEG) coating. This system improves drug efficacy by concentrating therapeutic agents at the tumour site, and can also induce ferroptosis in cancer cells, an iron-dependent cell death process, which has a beneficial therapeutic effect. Additionally, PEG molecules on the surface of MNPs facilitate drug conjugation for targeted delivery to cancer cells. These MNPs were designed as a delivery system for antitumoral drugs like irinotecan, carboplatin and cisplatin for personalized therapies. Based on the obtained results, it was found that the functionalization with glutamic acid and stabilization with PEG can improve the internalization efficiency of the magnetic carriers into the tumour cells. Owing to their stability, the MNPs can reach and penetrate mitochondria and organize around lipid vesicles, with the most effective results observed for the cisplatin-loaded system from a concentration of 0.1 mg/mL.
Keywords: drug delivery; magnetic nanoparticles; glutamic acid; antitumoral agents; personalized treatment; cisplatin; carboplatin; irinotecan